Persistent elevation of D-Aspartate enhances NMDA receptor-mediated responses in mouse substantia nigra pars compacta dopamine neurons. (April 2016) - Krashia, Paraskevi; Ledonne, Ada; Nobili, Annalisa; Cordella, Alberto; Errico, Francesco; Usiello, Alessandro; D'Amelio, Marcello; Mercuri, Nicola Biagio; Guatteo, Ezia; Carunchio, Irene
Abstract: Dopamine neurons in the substantia nigra pars compacta regulate not only motor but also cognitive functions. NMDA receptors play a crucial role in modulating the activity of these cells. Considering that the amino-acid D-Aspartate has been recently shown to be an endogenous NMDA receptor agonist, the aim of the present study was to examine the effects of D-Aspartate on the functional properties of nigral dopamine neurons. We compared the electrophysiological actions of D-Aspartate in control and D-aspartate oxidase gene ( Ddo −/− ) knock-out mice that show a concomitant increase in brain D-Aspartate levels, improved synaptic plasticity and cognition. Finally, we analyzed the effects of L-Aspartate, a known dopamine neuron endogenous agonist in control and Ddo −/− mice. We show that D- and L-Aspartate excite dopamine neurons by activating NMDA, AMPA and metabotropic glutamate receptors. Ddo deletion did not alter the intrinsic properties or dopamine sensitivity of dopamine neurons. However, NMDA-induced currents were enhanced and membrane levels of the NMDA receptor GluN1 and GluN2A subunits were increased. Inhibition of excitatory amino-acid transporters caused a marked potentiation of D-Aspartate, but not L-Aspartate currents, in Ddo −/− neurons. This is the first study to show the actions of D-Aspartate on midbrain dopamine neurons, activating not only NMDA but also non-NMDA receptors. Our data suggest that dopamine neurons, under conditions of high D-Aspartate levels, build a protective uptake mechanism to compensate for increased NMDA receptor numbers and cell hyper-excitation, which could prevent the consequent hyper-dopaminergia in target zones that can lead to neuronal degeneration, motor and cognitive alterations. Highlights: Midbrain dopamine (DA) neurons have a key role in regulating movement and cognition. D-Asp can act as an agonist in DA cells, activating NMDA and non-NMDA receptors. D-Asp oxidase deletion in mice does not alter intrinsic properties of DA neurons. Ddo −/− DA neurons show enhanced levels of NMDA receptor subunits and NMDA currents. Ddo −/− DA neurons show enhanced D-Asp-specific uptake by amino-acid transporters.